Optimization of Xylitol Production by Candida tropicalis A26 - Wanlapa Lorliam (Science Faculty of Chiang Mai University, 2019)
Factors affecting xylitol production by Candida tropicalis A26 was investigated using Plackett-Burman design. According to 5 variables; media ingredients (3 variables), inoculums and pH; xylose and peptone were critical parameters affected on the xylitol production. Central composite design (CCD) was applied to screen for an optimal concentration of xylose and peptone. The highest xylitol production in flask scale was 42.52 g/l when xylose and peptone were 80 g/l and 4 g/l, respectively. The statistical regression model predicted the maximum xylitol production with 43.27 g/l, while the observed one was 42.52 g/l. Moreover, the production was scale up to 5 L by using stirred fermenter under the optimized condition. The highest xylitol production and xylitol yield were 71.59 g/l and 0.89 g/g xylose, respectively after 42h cultivation. The results of statistical model and 5L fermenter indicated that the optimized medium increased xylitol yield up to 1.45 folds compared with an un-optimized condition. Experimental design was successful by applied for improvement of xylitol production by C. tropicalis A26.